(3Yde GdJQHjI GdYGes (3ejGOjfg haQhYg (B/s - (3SYjO, CHh WGdH eMeOs; (3YHO GdNGdb, QTQGT CfjSs ((3HjQhJ (B:s (3OGQ GdfgVI GdYQHjI,s, 2001)
(3EWGQ eaghej JGQjNj(B.s
(3HHdjhLQGajI (B: (3U(B. 207-219.s
Keywords: (3GdJQHjIs; (3GdJYdjes